BANK LENDING OF INDUSTRIAL ENTERPRISES: ECONOMIC NATURE AND PRINCIPLES OF ITS REALIZATION - Herasymenko , Alina (Socio-economic relations in the digital society, 2021)
Abstract. Industrial enterprises and banks operate in the conditions of modern realities which reflect the consequencesof prolonged socio-economic and political instability. Industrial sector of economy is the object of strategicallyimportance of the state development in developed countries all over the world. At the same time, theindustrial sector of economy is tended to be very sensitive to any fluctuations in the both financial and commoditymarkets, as well as to changing scenarios in the socio-economic and political environments. There arealso a number of essential obstacles that hinder development of the former Soviet Union industrial enterprises’productive and economic potential. Here is some of it: outdated material and technical base, lack of innovativetechnologies, lack of their own financial resources, high level of energy consumption, poor understandingof the ecology policy issue or its absence, and so on. Such a state reduces the chances of successful developmentof industrial enterprises’ productive and economic potential significantly. One of the efficient and forcefulways of improvement of overall socio-economic situation in the country is development, stable support andmodernization of industrial enterprises on the basis of mutually beneficial cooperation of banks’ and industrialenterprises’ capitals. A special role in these processes should be given to a variety of instruments of financial andcredit markets. One of these instruments is a bank lending to industrial enterprises. Herewith, the main accentshould be made on the role of bank lending to industrial enterprises. Since any elaboration of subject first of allrequires a strong opinion of its economic nature, the term «bank lending to industrial enterprises» is researchedin this issue, as well as specific principles of bank lending to industrial enterprises.Keywords: industry, industrial enterprise, loan, lending to enterprises, lending to industrial enterprises, banklending to industrial enterprises.JEL Classification G21, E51, P42Formulas: 0; fig.: 2; tabl.: 0; bibl.: 21.
Keywords: industry; industrial enterprise; loan; lending to enterprises; lending to industrial enterprises; bank lending to industrial enterprises